Traditional resistance training versus torque training: A randomized controlled trial - de Pablos, R.; García Pallarés, J.; Brea Alejo, L.; Martínez Cava, A.; Valenzuela, P.; Rodríguez Sánchez-Redondo, I.; Revuelta, C.; Lucía, A.; Barranco Gil, D. (Journal of Science and Cycling, 2025)
Resistance training (RT) has been shown to improve endurance performance in cycling. Notably, it has been recommended that cyclists perform heavy (>70% of one-repetition maximum [1RM]) RT sessions off the bike to optimize neuromuscular adaptations. On the other hand, the so-called "torque" training (i.e., low-cadence efforts performed against an allegedly high pedaling intensity) has become increasingly popular as an on-bike alternative to conventional (off-bike) RT for enhancing lower-limb muscle strength and cycling performance. However, recent evidence suggests that the force demands of this torque training on lower-limb muscles are relatively low (i.e., <50% of the cyclists` maximal lower-limb dynamic force), and its effectiveness compared to training at similar relative intensities but with self-selected cadences remains unclear. This study compared the effects of off-bike RT (squats) and torque training on endurance-related parameters in well-trained cyclists. Twenty-seven male cyclists were randomly assigned to off-bike RT (n = 9), torque training (n = 9), or a control group (n = 9) for 10 weeks. The RT group performed 5 sets of 7 squats at 70% 1RM twice per week, with a 4-minute intraset recovery, while the torque group completed 5 sets of 4-minute intervals at 70% VO2max power output at a target cadence of 50rpm, with a 2-minute intraset recovery, twice a week. Measured outcomes included VO2max, maximal aerobic power (MAP), ventilatory thresholds (VT, RCP), and time to exhaustion at RCP. Off-bike RT significantly improved MAP (p = 0.05, ES = 0.60), VT (p < 0.05, ES = 0.47), and RCP (p = 0.05, ES = 0.48). No significant changes were observed in the torque training group and control group. These findings indicate that off-bike RT is a superior method for improving pedaling performance, highlighting its importance in cycling training. Future research should refine torque training protocols to enhance its efficacy.